Fabrication of novel kaolin-reinforced hydroxyapatite scaffolds with robust compressive strengths for bone regeneration - Salami Kazeem Adeniyi; David O Obada; Semiyou A Osseni; Haziz Sina; Ayodeji N Oyedeji (Elsevier, 2021)
In this study, hydroxyapatite (HAp) microparticles obtained from animal bones were synthesized, and for the first time, HAp was reinforced with beneficiated kaolin using the sol-gel route to improve the mechano-biological properties of the bioceramic materials. The non-reinforced HAp as well as the reinforced samples (K-HAp) were sintered at 900, 1000 and 1100 °C to consolidate the mixture and detailed physico-chemical and mechanical characterizations was conducted. In-vitro experiments in phosphate buffer saline and simulated body fluid were used to confirm the degradability and compatibility of the HAp-derived bioceramic materials, respectively. XRD signatures showed that a dominant phase of hydroxyapatite was formed at all sintering temperatures (900, 1000, 1100 °C). The calcium to phosphate ratio (Ca/P) of the K-HAp-900 sample was approximately 1.67, which is the Ca/P ratio for stoichiometric …